St. Louis Paper - The Mechanical Preparation of Anthracite - Richard P. Rothwell (The American Institute of Mining, Metallurgical, and Petroleum Engineers)
The anthracite coals of Pennsylvania are all mined from large veins. A seam less than four feet. in thickness is generally considered as unworkable, those from which most of the coal now comes being from 8 'to 30 feet thick. The system of mining employed is, almost without exception, that known as " chamber and pillar work;" that is, the coal is taken out of chambers of from 18 to 30 feet in width, and pillars of from 12 to 20 feet are left between these to support the roof. In general, the entire thickness of the seam, even